CRITICAL REVIEW OF THE ROLE OF TELEMEDICINE IN EMERGENCY CARE - Abdullah Ali Mohammad Khiswi, Mahdi Hadi Bin Mahdi Alsallum, Ali Mansour Bin Hamed Alyami, Abdullah Mana Bin Salem Alyami, Ali haider mahdi alhottila, Mansour Hadi Ali Lsllum, Ogab Ali Ahmad Al obeed, Rayan sadaan alyamyi, Dafer Hussain Hadi al Dalan; Jaber Hussain Ali bin humayyim (Chelonian Research Foundation, 2023)
The function of telemedicine in an emergency has progressively improved in recent years and is strongly transforming healthcare delivery, especially in emergency rooms. The critical review will cover different areas of emergency care in which telemedicine has been found to have a significant impact; this will include the coordination of nursing and emergency staff, technicians, administration, respiratory medicine, and doctors to bring care to patients in a timely and efficient manner. Telemedicine in nursing and emergency specialty medical practitioners can vary in these areas of our occupation and performance (Haleem et al., 2021). The critical review examines the many advancements in remote patient monitoring, virtual consultations, and real-time communications, analyzing their impact on patient outcomes, efficiency of care, and the overall quality of emergency care. Analyzing the extent to which technology applies to the training of emergency technicians and skill development is also important. Telemedicine has altered the information flow and organization in medical emergency care. The main part of the paper critical analysis- aims to identify the effect on the work discipline, workflow improvement, and administrative decision-making. The introduction of telemedicine solutions in respiratory therapy beyond emergency scenarios and assessing its impact on quick diagnostics, intervention, and monitoring of patients with breathing disorders is also discussed in this study (Dóra et al., 2023). Telemedicine has also blurred the boundaries among diverse healthcare professionals, making them cooperate. Depending on the situation, the latter covers a nurse's relationship with emergency techs, specialists, and doctors. This evaluation appraises team-based virtual care and problems and opportunities for communication, decision-making, and coordination of interventions, which are improved by setting up patient outcomes. In extension, the Emergency Room is where collaboration between emergency technicians and nurses, in addition to ways for communication, is primordial. The review's core problem is stereotyping telemedicine's contribution to care cooperation. Thus, it is a very efficient tool that improves the accuracy of diagnostics, treatment planning, and patient management. A major focus is laid on the application of telemedicine in the usual operations of the emergency room, where issues are discussed concerning the complexity and the unpredictability of the future. Keywords: nursing, emergency specialists, telemedicine, technicians, administration, respiratory